ضرورة تفعيل دور محافظ الحسابات للحد من المخاطر البيئية للمؤسسات في الجزائر - زهواني, رضا (جامعة الوادي - University of Eloued, 2016)
تهدف هذه الدراسة إلى ضرورة تفعيل دور محافظ الحسابات في المؤسسات للحد من المخاطر البيئية الذي يعتبر بمثابة الركيزة التي تحمي الاقتصاد الوطني، ونظرا للدور الذي يقوم به في زيادة الثقة في مخرجات المؤسسة ومحاربة أشكال المخاطر البيئية التي تحيط بها، وعلى الرغم من الدور والاستلزامات الذي يقوم به محافظ الحسابات والتي تفرض عليه من استقلالية وحيادية في إبداء الرأي عن المعلومات المالية تجاه المؤسسة إلا أن هذه المعلومات لم تعد كافية لتشخيص وضعية المؤسسة تجاه البيئة التي تنشط فيها، ولذا أصبح لزاما من سن قوانين وتشريعات جديدة لمهنة محافظ الحسابات تعمل على تكييف وإدراج المعلومات البيئية ضمن صلاحيات محافظ الحسابات من خلال التشخيص والمراقبة والإفصاح عن المعلومات البيئية في التقارير المالية. the necessity of activating the role of the governor of the accounts in the institutions to limit the environmental hazards which is considered as a substrate that protects the national economy. And because of the role they play in increasing confidence in the institution's outputs and the fight against environmental risks that surround it, and despite the role and obligations which are done by the Governor of the accounts, which imposes upon him the independence and impartiality of the express an opinion on toward the institution of financial information, however, this information is no longer sufficient to diagnose the status of the institution towards the environment where they are active. So it is imperative to enact new laws and legislations for the career of the governor of accounts working to adapt and integrate environmental information within the powers of the governor of accounts through the diagnosis, monitoring and disclosure of environmental information in the financial reports
مقال
Keywords: محافظ الحسابات، المخاطر البيئية، أساليب حماية البيئة، تكييف القوانين والتشريعات لمهنة محافظ الحسابات ذات صلة بالبيئة; governor of the accounts, environmental risk, environmental protection methods, adapting laws and regulations for the governor of accounts related accounts.